Nonlocal boundary-value problems for systems on linear partial differential equations - Goi, T. P.; Ptashnik, B. I. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We study the classical well-posedness of problems with nonlocal two-point conditions for typeless systems of linear partial differential equations with variable coefficients in a cylindrical domain. We prove metric theorems on lower bounds for small denominators that appear in the construction of solutions of such problems.